2009
DOI: 10.1016/s2255-4971(15)30049-5
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Treatment of Acromioclavicular Joint Dislocation by Tight Rope Technique (Arthrex®)

Abstract: Presenting the arthroscopic treatment by Tight Rope - Arthrex® system for acute acromioclavicular dislocation and to evaluate results obtained with this procedure. Methods: Between August 2006 and May 2007, 10 shoulders of 10 patients with acute acromioclavicular dislocation were submitted to arthroscopic repair using the Tight Rope - Arthrex® system. Minimum follow-up was 12 months, with a mean of 15 months. Age ranged from 26 to 42, mean 34 years. All patients were male. Radiology evaluation was made by trau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 17 publications
0
11
0
3
Order By: Relevance
“…Fueron valorados mediante la escala de UCLA con puntajes en promedio de 32.5, los cuales son satisfactorios, al igual que los obtenidos en este trabajo. 14 Saier y colaboradores realizaron un trabajo de investigación para evaluar el retorno a la actividad posterior a la intervención quirúrgica, mediante las escalas DASH y Constant. Tomaron en cuenta el retorno a la actividad física parcial, completa y competitiva.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Fueron valorados mediante la escala de UCLA con puntajes en promedio de 32.5, los cuales son satisfactorios, al igual que los obtenidos en este trabajo. 14 Saier y colaboradores realizaron un trabajo de investigación para evaluar el retorno a la actividad posterior a la intervención quirúrgica, mediante las escalas DASH y Constant. Tomaron en cuenta el retorno a la actividad física parcial, completa y competitiva.…”
Section: Discussionunclassified
“…Debido a esto, se empezaron a emplear técnicas con estabilización dinámica que usan injertos, suturas y anclas mediante cirugía artroscópica y abierta, con resultados mejores que los de la estabilización estática. 8,9,10,11,12,13,14 En nuestro hospital, según cifras del Sistema de Información Médico Operativo (SIMO) del Instituto Mexicano del Seguro Social, año 2016, la luxación de hombro tuvo una tasa de incidencia de 57.42 casos/10,000 egresos hospitalarios, así la luxación acromioclavicular grado III, IV, V y VI fue de 11.15/1,000 pacientes hospitalizados; se desconocen los tiempos de incapacidad laboral y de incorporación de los trabajadores a sus actividades. También se utilizan otras técnicas quirúrgicas para su manejo, como la técnica de Mumford, en la que se hace una resección distal de la clavícula con resultados no satisfactorios, por lo que se decidió realizar este es-tudio, cuyo objetivo es analizar los resultados funcionales de la colocación del sistema de anclaje doble botón TighRope (Arthrex Inc., Naples Florida USA) como implante para el tratamiento de la luxación acromioclavicular grado III, en población joven laboralmente activa (Figura 1).…”
Section: Introductionunclassified
“…These techniques can be done through open, minimally invasive, 14 or arthroscopic surgery. 15 , 16 The advantage in the use of anchors is its placement closer to the anatomical insertion site of the coracoclavicular ligaments. 17 …”
Section: Introductionmentioning
confidence: 99%
“…24 However, it also has flaws, such as a sawing effect of synthetic material because of clavicle rotation that can result in adhesive capsulitis, and since its approach is quite invasive to the coracoid base and can cause anterior subluxation of the clavicle, it can lead to a malreduction of the AC joint postoperatively. 1,10,11 It has been reported that these 2 surgical techniques have good anatomic healing of the CC ligament 9,16,21,23 ; however, a 2020 systematic review reported better functional outcomes and pain scores for suture button fixation than HP fixation. 29 In this study, we aimed to compare the long-term clinical and radiological outcomes of HP and TR fixation for AC joint dislocations.…”
mentioning
confidence: 99%
“… 24 However, it also has flaws, such as a sawing effect of synthetic material because of clavicle rotation that can result in adhesive capsulitis, and since its approach is quite invasive to the coracoid base and can cause anterior subluxation of the clavicle, it can lead to a malreduction of the AC joint postoperatively. 1 , 10 , 11 …”
mentioning
confidence: 99%